2022
DOI: 10.21744/lingcure.v6ns3.2144
|View full text |Cite
|
Sign up to set email alerts
|

Development of android-based gymnastics learning media to improve the ability to roll ahead straddle students in gymnastic learning

Abstract: This research aims to develop a valid, practical, and effective gymnastics learning medium to improve the ability to roll ahead to students on gymnastics learning. The development process of this model refers to the Plomp development model. The subject of the study is a student of the Department of Sports Education, Faculty of Sports Sciences. Data collection techniques use tests, interviews, questionnaires, and observations. The collected data is then analyzed quantitatively using the t-test. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Previous studies reported that technology in the sports sector is a complex system for collecting and processing large amounts of data (Camomilla, Bergamini, Fantozzi, & Vannozzi, 2018;Ratten, 2020). It aims to improve sports performance, where its use has been proven effective in sports training (Firdaus & Mario, 2022;Handayani et al, 2023;Kokarev, Kokareva, Atamanuk, Terehina, & Putrov, 2023;Lisenchuk et al, 2023;Oh, Johnson, & Syrop, 2019). Another study reported that sensor technology benefits transparent and objective measurement results (Eitzen, Renberg, & Faerevik, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that technology in the sports sector is a complex system for collecting and processing large amounts of data (Camomilla, Bergamini, Fantozzi, & Vannozzi, 2018;Ratten, 2020). It aims to improve sports performance, where its use has been proven effective in sports training (Firdaus & Mario, 2022;Handayani et al, 2023;Kokarev, Kokareva, Atamanuk, Terehina, & Putrov, 2023;Lisenchuk et al, 2023;Oh, Johnson, & Syrop, 2019). Another study reported that sensor technology benefits transparent and objective measurement results (Eitzen, Renberg, & Faerevik, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the use of technology in sports is increasing (Kim & Ko, 2019;Szymanski, Wolfe, Danis, Lee, & Uy, 2020), and its innovation have become an essential part (Alnedral, Ihsan, Mario, Aldani, & Sari, 2023;Handayani, Myori, Yulifri, Komaini, & Mario, 2023;Ratten, 2020). This aims to reduce errors in data collection (Firdaus & Mario, 2022), and facilitate performance improvements (Ferreira, Fernandes, Ratten, & Miragaia, 2020;Wang, Chen, & Lin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This research was conducted at SMA Addaraen Makassar with the research subjects being students of class X SMA with a total of 20 people as a limited trial place. The research procedure used is the plomp development model (Handayani et al, 2022). In the following, the research procedure is presented in the form of an image.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the basic service media that gains the best response is an android-based considering the character of generation Z and Alpha currently is in urgent need of educational media and counseling guidance services that are appropriate for the adolescent psyche using language of the adolescent development. (Rofi'ah & Widatiningsih, 2021); (Setianingsih & Naimah, 2021), (Maharani, 2022); (Handayani et al, 2022); (Mataka & Taibu, 2020), (Goldstein et al, 2022).…”
Section: Final Product Revisionmentioning
confidence: 99%